24.3: Understanding and Achieving Reproducibility for the Evaluation of Display Sparkle Contrast. (24th February 2021) - Rotscholl, Ingo; Rasmussen, Jens; Rickers, Christoph; Brinkmann, Julia; Liu, Bob; Krüger, Udo
Abstract : The reproducible quantification of anti‐glare layer based display sparkle with Imaging Luminance Measurement Devices (ILMD) is essential for testing and conformity assessment of many displays aiming at outdoor applications. This study systematically researches relevant setup and system influences of a Fourier space‐based sparkle evaluation. These include 13 different antiglare layers, two displays with different PPI, and several different system setups featuring 12 different camera/lens combinations and more than 10000 individual luminance images. Based on the resulting sensitivities, the measurement procedure is optimized with respect to the achieved reproducibility. The resulting procedure serves as basis to define a new automotive specification for reproducible sparkle measurements and may do so for other applications, that need to quantify sparkle in a reproducible way.